Multi-Factor Authentication Using Blockchain: Enhancing Privacy, Security and Usability - Muhammad Faisal; Irenna Wanisha; James, Jaymaxcklien Bravyain; Witeno, Jeremy Silas; Mohammad Bakery, Luqmanul Hakim; Samuel, Melvianna (International Journal of Computer Technology and Science, 2024)
In the ever-changing digital world, strong security protocols are essential. As a vital line of defence against unwanted access, blockchain uses several verification techniques to boost security. This article investigates the use of blockchain technology to tackle privacy, security, and usability issues. By reducing the dangers associated with conventional centralised systems, blockchain's decentralised and immutable structure offers a secure platform for storing and verifying authentication credentials. This method increases user trust by using smart contracts to guarantee transparent and unchangeable authentication procedures. The suggested blockchain-based method strengthens security and enhances privacy by removing sources of failure and decreasing dependence on outside verification. Furthermore, user-centric design and expedited procedures improve the system's usability by making secure authentication more approachable and less obtrusive. This paper offers a thorough examination of the suggested system, stressing its benefits, possible drawbacks, and directions for future investigation. The results indicate that blockchain technology presents a viable solution to ensure that digital authentication frameworks combine privacy, security, and usability.